2013
DOI: 10.1186/2193-1801-2-57
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and histopathological study in rats intoxicated with carbontetrachloride and treated with camel milk

Abstract: The unique characters of camel’s milk make it used extensively in the field of medicine as anti-microbial, anti-diabetic and hepatoprotective agent. The lack of studies demonstrating the protective effect of camel’s milk against hepatotoxic compound was the main reason beyond the conduction of the current experiment which aimed to investigate the protective effects of camel’s milk against carbontetrachloride (CCl4) induced hepatotoxicity. Therefore, 24 rats were fed on standard diet and divided into four group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 46 publications
10
44
0
Order By: Relevance
“…Moreover, Masson's trichrome stain of liver sections showed congestion and thickening of the portal tract with dense fibrous tissue. Similar observations of the liver tissues in CCl 4 intoxicated rats were reported previously (Domitrovic et al, 2009;Althnaian et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, Masson's trichrome stain of liver sections showed congestion and thickening of the portal tract with dense fibrous tissue. Similar observations of the liver tissues in CCl 4 intoxicated rats were reported previously (Domitrovic et al, 2009;Althnaian et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…As previously reported, administration of CCl 4 for 8 weeks resulted in a significant increase in serum ALT, AST activities as well as total billirubin levels (Mehmetcik et al, 2008;Arici and Cetin, 2011). Damaged liver architecture can lead to an increase in the serum activities of liver enzymes due to their localization in the cytoplasmic area of the cell (Althnaian et al, 2013). Theses biomarkers showed major improvement to near normal values with triplet combination, which is an indication of the stabilization of the plasma membrane and the repair of hepatic tissue damage caused by CCl 4 intoxication.…”
Section: Discussionmentioning
confidence: 97%
“…(Figure 3b, 3c and 3d). Histopathological results of CCl4 were similar to Al-Ghamdi [27], Eidi et al, [28], Soujanya et al, [29], Cordeiro¹ and Kaliwal¹ [30], Althnaian et al, [31] and Abdel et al, [32].From the histopathological examination of the present work it could be concluded that broccoli powder with escitalopram drug treated group showed minimal congestion of central vein and portal vein with minimal hepatocyte necrosis near the central vein [24] …”
Section: Discussionsupporting
confidence: 72%
“…1,9,11,12,13,14 Herbal extracts have been reported to ameliorate hepatic and renal disorders in humans and animal models. 2,9,13,15 There is a vast array of Nigerian indigenous medicinal plants that are used for the treatment and management of pathologic conditions linked with overwhelming levels of reactive metabolic radicals.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,7,8,9 Carbon tetrachloride (CCl 4 ) is a chemical agent noted to be toxic to hepatorenal tissues in experimental animals and human subjects. 5,6,8,10,11,12,13 Reports showed that CCl 4 toxicity is elicited by microsomal CYP2E1-induced formation of reactive trichloromethyl (CCl 3…”
Section: Introductionmentioning
confidence: 99%